1968
DOI: 10.1128/jvi.2.4.346-356.1968
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Bacteriophages to Adhesions Between Wall and Membrane of Escherichia coli

Abstract: In plasmolyzed Escherichia coli, wall and membrane adhered to one another at 200 to 400 localized areas. This number of specialized wall areas per cell was of the same order of magnitude as the total number of bacteriophage receptors. When bacteriophages TI to T7 were adsorbed to the bacteria, they were seen to attach almost exclusively to these areas. Comparisons of the number of adsorbed phage particles observed in ultrathin sections and the expected number of phages per cell were in agreement. These results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
1

Year Published

1971
1971
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(41 citation statements)
references
References 28 publications
2
38
0
1
Order By: Relevance
“…where the inner and outer membranes appear to touch; these are the adsorption sites for many bacteriophage (22,23).…”
Section: Mechanism Of Transfection and Helped Transfection Structure mentioning
confidence: 99%
“…where the inner and outer membranes appear to touch; these are the adsorption sites for many bacteriophage (22,23).…”
Section: Mechanism Of Transfection and Helped Transfection Structure mentioning
confidence: 99%
“…LPS transport has been suggested to proceed via putative proteinaceous contact zones between the IM and the OM (Muhlradt et al, 1973;Ishidate et al, 1986). These contact sites were first observed by Bayer (1968), and so they are often referred to as 'Bayer bridges'. LPS transport to the OM can be observed in spheroplasts of Escherichia coli, whereas phospholipid transport is not observed under the same experimental conditions (Tefsen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, all of the receptors would be fully functional. Bayer has reported that about 5% of the outer membrane is occupied by about 200 to 400 sites of fusion to the inner membrane, and that several phage receptors, including that for BF23 (personal communication), are located predominantly at these fusion sites (1,2). Some, if not all, ofthese sites evidently participate in the insertion of nascent lipopolysaccharide into the outer membrane (15), and Leive (personal communication) found that the specific activity for B12 binding was no greater at these insertion sites than in the rest of the outer membrane.…”
mentioning
confidence: 99%